Consensual Sexual Activity before a Sexual Violation is not Mitigating - McGovern, Danica (Victoria University of Wellington Law Review, 2023)
The Court of Appeal has signalled its intention to review its guideline judgment for sexual violation sentencing, R v AM, which includes guidance on when sentencing judges should treat prior consensual sex as mitigating. The argument this article makes is that the new guideline judgment should remove prior consensual sex as a mitigating factor for two reasons. The first is that treating consensual sexual activity before a sexual violation as mitigating embeds an outdated idea of what constitutes a "real rape" and fails to recognise and uphold sexual autonomy. The second reason for removing the mitigating factor is that it is incorrect as a matter of sentencing methodology to treat prior consensual sex as mitigating in its own right.